2001
DOI: 10.1007/s00216-001-1107-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance of permanent iridium modifier in the presence of corrosive matrix in graphite furnace atomic absorption spectrometry

Abstract: The influence of up to 16% HNO3, 28% HCl, and the mixture of both acids in aqua regia on the analytical performance of electrodeposited modifiers (Ir or Ir+Pd) was evaluated and discussed. Cadmium was used as an example of volatile elements often determined by graphite furnace atomic absorption spectrometry (GF AAS). In the presence of HCl, the maximum pyrolysis temperature that could be applied was found to be 600 degrees C. In the presence of HNO3 and aqua regia, both modifiers stabilized cadmium up to 800 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…10 It was found that the electrodeposition of noble metals on a graphite surface significantly improves the performance in the presence of a corrosive matrix. 20,21 Noble metals stabilize the analyte and act as permanent modifiers via the formation of intercalation compounds in the subsurface layer of pyrographite. Penetration is more pronounced using electrodeposition, since this forces the transportation of noble metals into the subsurface domain of the graphite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 It was found that the electrodeposition of noble metals on a graphite surface significantly improves the performance in the presence of a corrosive matrix. 20,21 Noble metals stabilize the analyte and act as permanent modifiers via the formation of intercalation compounds in the subsurface layer of pyrographite. Penetration is more pronounced using electrodeposition, since this forces the transportation of noble metals into the subsurface domain of the graphite.…”
Section: Introductionmentioning
confidence: 99%
“…Penetration is more pronounced using electrodeposition, since this forces the transportation of noble metals into the subsurface domain of the graphite. [21][22][23] The goal of this work was to utilize the advantages of an electrochemical modification of a graphite surface for mercury determination in environmental materials, such as soils, sediments and plant by using SS-ETAAS. Electrochemical procedures in cells and in drops for modifying the solid sampling (SS) platform surface were investigated and optimized.…”
Section: Introductionmentioning
confidence: 99%
“…An expected advantage of the modifier is improved long-term performance, and it was justified that noble metals modifiers could be used for this purpose [13][14][15]. It was found that electrodeposition of noble metals on the graphite surface offers significantly improved performance in the presence of a corrosive matrix [16,17]. According to the current understanding of the mechanism of the interaction between noble metals and graphite, they stabilize the analyte and act as permanent modifiers via the formation of intercalation compounds in the subsurface layer of pyrographite [9,10,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Penetration of noble metals within the pyrographite domain is expected to occur immediately after injection of the modifier solution, at the sampling/drying stage, due to the porosity of the pyrographite and nanometer scale cracks on the virgin pyrographite surface. This is even more pronounced using electrodeposition to introduce the modifier, since this forces the transportation of noble metals into the subsurface domain of the graphite [10,17].…”
Section: Introductionmentioning
confidence: 99%
“…17 Other permanent modifiers based on iridium have also proved to be very suitable for the determination of cadmium in complex matrices. 32,33 Pd-base modifiers have usually been the accepted choice. Using the Pd-Mg modifier in combination with ammonium nitrates, 14 up to 3000 mg L -1 NaCl did not interfere in the determination of Cd.…”
Section: Introductionmentioning
confidence: 99%